2003
DOI: 10.32398/cjhp.v1isi.565
|View full text |Cite
|
Sign up to set email alerts
|

Improving Native Hawaiian Health Through Community-Based Participatory Research

Abstract: Native Hawaiians, representing 20% of Hawai'i's population, have higher mortality rates and lower life expectancy than all other ethnic groups in Hawai'i and most ethnic groups in the United States. Although research is needed to reduce health disparities, past research abuses have led to feelings of distrust among many Native Hawaiians toward traditionally conducted research. 'Imi Hale-Native Hawaiian Cancer Awareness, Research and Training Network was established in 2000, one of 18 Special Population Network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 18 publications
(30 reference statements)
0
59
0
Order By: Relevance
“…13 As a result, new models of research have emerged highlighting the potential of community-engaged research and the need to build the capacity among researchers to engage respectfully, ethically, and meaningfully with communities. 4–8 Gaining a better understanding of how researcher capacity can be enhanced from community perspectives may help in more effectively addressing health disparities in minority communities. 9,10 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 As a result, new models of research have emerged highlighting the potential of community-engaged research and the need to build the capacity among researchers to engage respectfully, ethically, and meaningfully with communities. 4–8 Gaining a better understanding of how researcher capacity can be enhanced from community perspectives may help in more effectively addressing health disparities in minority communities. 9,10 …”
mentioning
confidence: 99%
“…8,2631 One such example is the Ulu Network, a community coalition formed in 2003 by The Center for Native and Pacific Health Disparities Research (The Center) at the University of Hawai‘i, John A. Burns School of Medicine’s Department of Native Hawaiian Health. 11,32 In the Hawaiian language ulu means to grow and it is also the name the breadfruit tree ( Artocarpus altilis ), which produces a popular Pacific produce.…”
mentioning
confidence: 99%
“…In a 2001 needs assessment involving 980 Native Hawaiians, genetic and biological research was identified as one of five priority issues for awareness and research [11]. However, participants were opposed to research that promotes outsider advancement, provides little or no benefit to participating communities, or uses results to stigmatize Native Hawaiians [12]. A 2004 survey of 357 Native Hawaiians assessed preferences for informed consent and disclosure of results from genetics research and compared findings against those from a White sample [13].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers working with Native Hawaiian populations in Hawaii have reported on a similar type of contamination and have described alternative methods such as focus groups and case studies to document outcomes of community-based participatory research efforts. 15,16 Last, there were several other limitations of this study that may have impacted our ability to detect differences in women's knowledge, beliefs, attitudes, and behaviors. First, we had a significant loss to follow-up (of 26.5%) of respondents during the study.…”
Section: Discussionmentioning
confidence: 91%